Does mandible ramus height asymmetry affect postoperative skeletal stability in orthognathic surgery patients? - Jihun Cha; Kyuwon Park; Jaeyoung Ryu; Seunggon Jung; Hong-Ju Park; Hee-Kyun Oh; Min-Suk Kook (SpringerOpen, 2024)
Abstract Background Relapses following orthognathic surgery have been reported to exceed 2% to 50%, depending on multiple factors. This study aimed to analyze the stability after orthognathic surgery in patients with mandibular ramus height asymmetry through 3D reconstruction using Cone-beam CT. Methods This retrospective cohort study investigated patients who underwent mandibular setback surgery using bilateral sagittal split ramus osteotomy. Three-dimensional CT scans were taken at three different time points. Evaluation of the postoperative stability involved measuring changes in the x, y, and z axes as well as roll and yaw rotations of the mandible at specific landmarks (B point, mental foramen) on 3D CT scans obtained immediately after surgery and 6-12 months postoperatively. They were categorized into four groups based on bilateral mandibular height asymmetry through Asymmetry index (AI). The one-way ANOVA was implemented to compare the intergroup differences and Tukey's post hoc test was employed. Additionally, the Pearson correlation coefficient was also calculated. Results A total of 24 patients were included in this study. The corresponding AI, representing the degree of asymmetry in both mandibles, were calculated as Group 1 was 1.25 ± 0.64%, Group 2 was 2.89 ± 0.47%, Group 3 was 5.03 ± 0.51%, and Group 4 was 9.40 ± 1.99%. The x-axis change in Group 4 was significantly larger at 1.71 mm compared to Group 1 at 0.64 mm. The mandibular roll, Group 4 showed a statistically significant increase at 1.33° compared to Group 1 at 0.35°. And there was a significant positive correlation observed between x-axis change and AI (p = 0.019), as well as between mandibular roll and AI (p = 0.025). Conclusion After orthognathic surgery, stability was influenced by numerous factors, with the findings of this study suggesting that the degree of ramus height asymmetry in the mandible can be considered one contributing factor.